An In-Depth Examination of Phytochemicals and Medicinal Uses on Morus alba - Dubey, Roshan Kumar; Shukla, Satyam; Shukla, Prashant (Chinese medicine and natural products, 2024)
Morus alba, commonly known as white mulberry, is a plant renowned for its diverse range of bioactive compounds that confer numerous health benefits. This review explores the plant's antioxidant, anti-inflammatory, anticancer, cardiovascular, neuroprotective, hepatoprotective, and antimicrobial properties. The antioxidant effects, primarily attributed to flavonoids, phenolic acids, and terpenoids, help mitigate oxidative stress and protect against various diseases. The anti-inflammatory properties reduce chronic inflammation, while the anticancer compounds induce apoptosis and inhibit tumor growth. Morus alba's cardiovascular benefits include improved endothelial function and lipid metabolism. Its neuroprotective effects protect the brain from oxidative damage and neuroinflammation, supporting cognitive function. The hepatoprotective activity enhances liver health and prevents damage from toxins. Additionally, the plant's antimicrobial properties make it effective against a broad spectrum of pathogens. Overall, Morus alba holds significant potential as a natural therapeutic agent, with applications in both traditional and modern medicines.
Keywords: Morus alba; white mulberry; antioxidant properties; anti-inflammatory effects; anticancer potential; cardiovascular health